Study and Scale Quality in Second Language Survey Research, 2009–2019: The Case of Anxiety and Motivation. Issue 4 (30th August 2021) - Sudina, Ekaterina
Abstract: Research on anxiety and motivation in second language (L2) learning is proliferating. However, these two individual differences are commonly measured by self‐report questionnaires, the psychometric properties of which have been questioned. Building on previous works on study quality, this methodological synthesis systematically describes and evaluates the state of study and scale quality in L2 anxiety and motivation research. A total of 104 peer‐reviewed articles (113 independent samples) that used 340 L2 anxiety and motivation scales were coded for 84 features targeting: study, survey, and scale designs; participant demographics; scale validity and reliability; and reporting practices associated with transparency. The results show a number of strengths but also reveal multiple areas in need of methodological enhancement. The article concludes by highlighting areas that merit further investigation in the domain of L2 survey research and making recommendations for future studies. Abstract :